Identification of Dyscalculia Characteristics Based on Mathematics Examination Results in Students with Physical Disabilities - Firmansyah, Gilang Risqi; Lutfiyah, Lutfiyah; Hidayatin, Nur (Journal of Education and Learning Mathematics Research (JELMaR), 2025)
Abstract: This study aims to identify and describe the characteristics of dyscalculia in seventh-grade students with physical disabilities at SLB-BCD YPAC Jember. Students with physical disabilities often face dual challenges, namely physical limitations and potential specific learning difficulties such as dyscalculia. Using a descriptive qualitative approach, this study analyzed data from mathematics exam results, in-depth interviews with accompanying teachers, and classroom observations. The subjects were two students with physical disabilities who showed indications of learning difficulties in mathematics. The results showed clear manifestations of dyscalculia characteristics in both subjects. The main findings include: (1) difficulties in comparing and ordering numbers (numerical aspect); (2) weaknesses in visual-spatial perception for recognizing geometric shapes (geometric aspect); (3) procedural errors in basic arithmetic operations such as subtraction involving the concepts of place value and borrowing; and (4) difficulties in applying mathematical concepts to practical word problems. The conclusion of this study confirms that students with physical disabilities can exhibit complex dyscalculia profiles, which require individually tailored assessment strategies and learning interventions.